Роль інноваційно-інвестиційних ресурсів у системі факторів ліквідності об’єктів - Дзюбенко, Л. І. (Ways to Improve Construction Efficiency, 2012)
The article discusses the basic resources of economic growth. The changes in the development of social production, the factors by which achieved growth of reproductive processes in the economy.